The Intermediary Role of Sustainable Development in the Relationship Between Good Governance and Performance Improvement: A Case Study of Municipalities in the Gaza Strip (Palestine) - Albhaisi, Abdalmoti Mahmoud; Alchouk, Souad Kamoun (Journal of Economic, Administrative and Legal Sciences, 2025)
This study aims to evaluate the extent to which the principles of good governance are applied in the municipalities of the Gaza Strip, and the extent of their impact on improving municipal performance within the framework of achieving sustainable development. The researcher adopted the descriptive-analytical approach, using a questionnaire to collect data from the study population, which consists of 2,863 employees in the municipalities of the Strip. A total of 339 questionnaires were distributed, 8 of which were excluded due to their unsuitability for statistical analysis. The data were analyzed using the SPSS program. The importance of the study lies in shedding light on the relationship between good governance and the improvement of municipal performance—an issue that has not been sufficiently researched—while focusing on the role of municipalities in providing services and enhancing quality of life. The study concluded that the municipalities in the Strip apply governance principles well, with an improvement in the quality of local governance. Transparency emerged as the most significant element in ensuring the integrity and effectiveness of decision-making and implementation, followed by justice and accountability. The results also demonstrated the importance of community participation and anti-corruption efforts as essential pillars for promoting governance. The study found a positive relationship between good governance and improved municipal performance and indicated that sustainable development reinforces this effect. It also showed that the assessment of anti-corruption efforts and performance improvement is influenced by factors such as experience and job title, with department heads being more satisfied than division heads. Furthermore, female respondents showed greater interest in sustainable development.